2011
DOI: 10.1111/j.1751-7176.2011.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Efficacy and Safety of Triple-Combination Therapy With Olmesartan, Amlodipine, and Hydrochlorothiazide: The TRINITY Ambulatory Blood Pressure Substudy

Abstract: This 12-week, multicenter, randomized, double-blinded, 4-arm study in 440 patients with moderate to severe hypertension compared ambulatory blood pressure (ABP) responses with a triple-combination regimen (olmesartan medoxomil [OM] 40 mg, amlodipine besylate [AML] 10 mg, and hydrochlorothiazide [HCTZ] 25 mg) and its component dual-combination regimens at similar doses. At week 12, the triple combination resulted in a greater reduction in mean 24-hour systolic and diastolic blood pressure ()30.3 ⁄)18.0 mm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…At 12 weeks, the triple-combination therapy resulted in significantly more BP reduction when compared with dual therapy, with no significant difference in adverse events 72. The 24-hour ambulatory BP substudies of the two trials discussed here confirmed significantly larger reductions in mean 24-hour, daytime, and nighttime systolic and diastolic BP in the triple-combination groups 73,74. Furthermore, in an open-label extension of the TRINITY trial, the triple-combination therapy allowed up to 80% of patients to achieve BP target after 52 weeks and was well-tolerated 75.…”
Section: Acceptable Combinationssupporting
confidence: 51%
“…At 12 weeks, the triple-combination therapy resulted in significantly more BP reduction when compared with dual therapy, with no significant difference in adverse events 72. The 24-hour ambulatory BP substudies of the two trials discussed here confirmed significantly larger reductions in mean 24-hour, daytime, and nighttime systolic and diastolic BP in the triple-combination groups 73,74. Furthermore, in an open-label extension of the TRINITY trial, the triple-combination therapy allowed up to 80% of patients to achieve BP target after 52 weeks and was well-tolerated 75.…”
Section: Acceptable Combinationssupporting
confidence: 51%
“…When the lower dose of chlorthalidone was used in the combination studies with azilsartan medoxomil, BP reductions were similar to those observed in the present study using the 5 mg dose of amlodipine in combination with azilsartan medoxomil 27. As shown previously, the combination of the angiotensin receptor blockers with either amlodipine or a thiazide diuretic will likely provide effective therapy for patients with more difficult-to-control hypertension 28,29.…”
Section: Discussionsupporting
confidence: 86%
“…Also, a significantly greater proportion of patients using triple therapy reached target blood pressures ( P < 0.001 versus dual combinations). Significantly greater reductions in mean 24-hour blood pressure were also observed for the triple combination compared with dual therapy ( P < 0.0001), showing that duration of action is increased as well as magnitude of effect 56. Triple combination therapy was well tolerated, with the majority of adverse events being mild-or-moderate in severity.…”
Section: Arb-based Combination Therapymentioning
confidence: 84%